Post-prandial decrease in plasma growth hormone levels is not related to the increase in plasma insulin levels in goats - Koki Nishihara; Ryoko Kobayashi; Yutaka Suzuki; Katsuyoshi Sato; Kazuo Katoh; Sanggun Roh (Asian-Australasian Journal of Animal Sciences, 2017)
Objective In the present study, we examined whether the post-prandial reduction in plasma growth hormone (GH) levels is related to the increase in plasma insulin levels in ruminants. Methods We performed two experiments: intravenous bolus injection of insulin (0.2 IU/kg body weight) or glucose (1.0 mmol/kg body weight) was administered to increase the plasma insulin levels in male Shiba goats. Results In the insulin injection experiment, significant (p<0.05) increase in GH concentrations was observed, 15 to 20 min after the injection; it was accompanied with a significant (p<0.01) increase in cortisol concentrations at 45 to 90 min, when compared to the concentrations in the saline-injected controls. The glucose injection significantly (p<0.05) increased the plasma GH concentration at 20 to 45 min; this was not accompanied by significantly higher cortisol concentrations than were observed for the saline-injected control. Hypoglycemia induced by the insulin injection, which causes the excitation of the adrenal cortex, might be involved in the increase in insulin levels. Conclusion Based on these results, we conclude that post-prandial increases in plasma insulin or glucose levels do not induce a decrease in GH concentration after feeding in the ruminants.